Determinación de contaminantes Atmosféricos producidos por motores Diesel utilizando Biodiesel obtenido de aceite de cocina reciclado generado por las Pollerías de Moyobamba, 2011 - Castillo Macedo, Christian Del (2011)
Air pollution is becoming greater and greater, being the main contributor the self-propelled park, which is why it is born the need to find viable alternatives for solution to replace in part the use of fossil fuels for combustion engines. For such a motive the formless present of thesis is dedicated to the determination of atmospheric pollutants produced by the diesel engines using biodiesel, being the gases when analyzing CO (Carbon monoxide), SO2(sulphur Dioxide) and NO2 (Dioxide of nitrogen), since these are the principal pollutants of the atmosphere exempting the CO2 (Carbon dioxide), for which specific equipment of measurement were in use for every gas, which were provided by UNSM-T.For that reason, the present thesis report is dedicated to the determination of atmospheric pollutants produced by diesel engines using biodiesel, being the gases to analyze the CO (carbon monoxide), SO2 (sulfur dioxide) and NO2 (nitrogen dioxide), since these are the main pollutants in the atmosphere except for the CO2 (carbon dioxide), which were used for measuring equipment specific to each gas, which were provided by, UNSMS -T. The measurements were realized in two levels of acceleration, which were taken every 15 minutes of functioning in an hour, in different concentrations of biodiesel (B-25, B-50, B-100), which were compared with the Diesel (B-5). It also took into account the economic viability of biodiesel, for which it was obtained the profitability and performance of the engines in use with biodiesel. Which it was concluded that the use of biodiesel is economically profitable, because the residue such as glycerin can be used for industry and this has an economic value. The performance was 96.16 % Biodiesel, obtaining a high performance. The purpose of the course is to understand what are the comparative differences in emissions, profitability and performance between biodiesel and conventional diesel that is typically used in cars The purpose is know which are the comparative differences of the emission, profitability and performance between biodiesel and conventional diesel that is typically used in cars, in which it was concluded that the use of biodiesel is significantly reduces the emissions of CO and SO2, and the issuance of NO2 increases, but with the use of this Diesel gas ecreases, with the results obtained provide conclusions and recommendations regarding the use of biodiesel at different concentrations (B25, B50 and B100) so that the impacts produced by the fleet are diminished with such use.